2016
DOI: 10.1210/me.2016-1039
|View full text |Cite
|
Sign up to set email alerts
|

Phoenixin Activates Immortalized GnRH and Kisspeptin Neurons Through the Novel Receptor GPR173

Abstract: Reproductive function is coordinated by kisspeptin (Kiss) and GnRH neurons. Phoenixin-20 amide (PNX) is a recently described peptide found to increase GnRH-stimulated LH secretion in the pituitary. However, the effects of PNX in the hypothalamus, the putative signaling pathways, and PNX receptor have yet to be identified. The mHypoA-GnRH/GFP and mHypoA-Kiss/GFP-3 cell lines represent populations of GnRH and Kiss neurons, respectively. PNX increased GnRH and GnRH receptor (GnRH-R) mRNA expression, as well as Gn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
93
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(102 citation statements)
references
References 59 publications
3
93
0
6
Order By: Relevance
“…A lately discovered novel endogenous neuropeptide, phoenixin (PNX), has been isolated and identified from multiple locations, such as the hypothalamus, in the brain (Yosten et al, ). PNX, which is post‐translationally processed from a relatively smaller integral membrane protein 20 (SMIM20), has been described to have regulatory implications on the reproductive system (Yosten et al, ) via G‐protein‐coupled receptor (GPCR; Treen, Luo, & Belsham, ). The first report about PNX indicated that the peptide is chiefly produced by hypothalamus and pituitary gland in the brain and a number of peripheral tissues (Yosten et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…A lately discovered novel endogenous neuropeptide, phoenixin (PNX), has been isolated and identified from multiple locations, such as the hypothalamus, in the brain (Yosten et al, ). PNX, which is post‐translationally processed from a relatively smaller integral membrane protein 20 (SMIM20), has been described to have regulatory implications on the reproductive system (Yosten et al, ) via G‐protein‐coupled receptor (GPCR; Treen, Luo, & Belsham, ). The first report about PNX indicated that the peptide is chiefly produced by hypothalamus and pituitary gland in the brain and a number of peripheral tissues (Yosten et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the recently discovered neuropeptide phoenixin, which is colocalized with NUCB2/nesfatin-1 in a number of hypothalamic nuclei (ARC, PVN, ventromedial and lateral hypothalamus) has been suggested as a potential mediator for nesfatin-1's action with regard to reproduction. Phoenixin increases GnRH, GnRH receptor and Kiss1 gene expression (Yosten et al 2013, Treen et al 2016 and potentiates GnRH-stimulated LH release in vitro (Yosten et al 2013). These findings were substantiated by an in vivo study demonstrating that i.c.v.…”
Section: Reproductionmentioning
confidence: 83%
“…Moreover, in vivo siRNA knockdown of phoenixin resulted in a delayed appearance of oestrus and a reduced expression of GnRH receptors in the pituitary [8] . More recently, the orphan G-protein coupled receptor GPR173 has been proposed as the primary receptor candidate mediating the reproductive effect of phoenixin [6,7] . Reproduction is controlled by the hypothalamic-pituitary-gonadal axis which responds to cues from energy stores.…”
Section: A Signaling Molecule In the Nervous Systemmentioning
confidence: 99%
“…Viewed in this context, a clear and present need for information relative to novel GPCRs and their endogenous ligands is obvious. Phoenixin is a recently discovered peptide ligand that is reported to target the GPR173 [6,7] . Similar to many peptide ligands, phoenixin is distributed broadly in the central and peripheral nervous systems with a particular concentration in the hypothalamus, spinal cord and myenteric plexus, establishing an anatomical as well a functional connection between the gut and brain.…”
Section: Prospectivementioning
confidence: 99%
See 1 more Smart Citation